The pioneering of intracytoplasmic sperm injection: historical perspectives. Issue 6 (December 2017) - Rosenwaks, Zev; Pereira, Nigel
Abstract : Intracytoplasmic sperm injection (ICSI) has often been heralded as a ground-breaking technique that has transformed the treatment of couples with infertility. By injecting a single spermatozoon into the cytoplasm of the oocyte, ICSI bypasses the zona pellucida and increases the chances of fertilization and subsequent embryo development, independent of semen parameters. Ever since the first live births using ICSI were reported in 1992, ICSI has become the mainstay of treating male factor infertility as well as overcoming fertilization failure associated with conventional in vitro insemination. Today, ICSI is utilized in nearly 66% of all assisted reproductive treatments worldwide and has resulted in the birth of millions of babies. The primary goal of this review is to provide historical perspectives about the pioneering of ICSI. We begin by highlighting the scientific work of early investigators who elucidated the mechanisms central to mammalian fertilization. Furthermore, we briefly discuss how these findings contributed to the development of IVF for the treatment of infertility. We then emphasize the shortcomings of IVF in treating severe forms of male factor infertility and enumerate the micromanipulation techniques that were developed to circumvent these shortcomings. Finally, we indicate how the inadequacies of these micromanipulation techniques lead to the inception, application and popularity of ICSI.